2007
DOI: 10.1002/chem.200701568
|View full text |Cite
|
Sign up to set email alerts
|

Response to “Comments on a Possible Transition to Solid‐Phase Homochirality”

Abstract: As part of an ongoing discussion comparing models for the evolution of homochirality, we address the preceding Correspondence by Ribó and co‐workers. We demonstrate that our previous Concept article did not include errors concerning solubility behavior and we address the challenge of representing equilibrium phase behavior for systems of racemizing enantiomers. In addition we re‐emphasize the point that the homochiral state is not inherently more stable than the heterochiral state and we show that concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…This contrasts with the anticipations in a recent report, though for a different reactive system 3e. 7…”
Section: Resultscontrasting
confidence: 97%
“…This contrasts with the anticipations in a recent report, though for a different reactive system 3e. 7…”
Section: Resultscontrasting
confidence: 97%
“…Notably, Viedma et al later demonstrated that continuous grinding of a slurry of a racemic mixture of enantiomorphic crystals could cause its deracemization to produce an enantiopure product (Viedma ripening) 1218 . Especially, Blackmond and coworkers for the first time experimentally supported a hypothesis of the emergence of solid-phase homochirality from racemic conglomerates composed of rapidly racemizing enantiomers 13,19,20 . Tsogoeva and coworkers achieved a complete deracemization (100% ee ) of an asymmetric reaction product by combining its reversible asymmetric reaction and physical grinding of crystals involved 21,22 .…”
Section: Introductionmentioning
confidence: 98%
“…While a stimulating scientific discussion on the fine details of the mechanism of symmetry breaking processes, both crystallization [37][38][39][40][41] and synthesis, [42][43][44][45] continues, theoretical reaction-type models have been developed that can describe the kinetics of the time evolution of a system toward homochirality. [46][47][48][49] Indeed, complete homochirality of products in a mirrorimage symmetry breaking process (whether crystallization or synthesis) can be designed as a result of non-linear autocatalysis coupled with back-reaction recycling of achiral substrates in a closed system.…”
Section: Introductionmentioning
confidence: 99%